2016
DOI: 10.1097/rhu.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Renal Thrombotic Microangiopathy in Proliferative Lupus Nephritis: Risk Factors and Clinical Outcomes

Abstract: Lymphopenia and anti-Ro positivity are independent risk factors for renal TMA in SLE patients. This increased risk could be a consequence of the potential role of these factors in endothelial dysfunction and damage. Outcomes were similar for patients with the same estimated glomerular filtration rate and biopsy characteristics, regardless of the presence of TMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
11
0
6
Order By: Relevance
“…Concurrent TMA has been observed in 8–15% of systemic lupus erythematosus (SLE) biopsies and was reported to have no influence on outcome [ 352 , 353 ] in some cohorts, but was associated with worse renal outcome in another [ 354 ]. In a mouse model of SLE, C5 inhibition increased survival [ 206 ]; in humans hypocomplementaemia correlates with disease activity [ 207 ], and CFHR3/1 deletion is associated with susceptibility to SLE [ 208 ].…”
Section: Evidence For the Role Of Complement In The Tmasmentioning
confidence: 99%
“…Concurrent TMA has been observed in 8–15% of systemic lupus erythematosus (SLE) biopsies and was reported to have no influence on outcome [ 352 , 353 ] in some cohorts, but was associated with worse renal outcome in another [ 354 ]. In a mouse model of SLE, C5 inhibition increased survival [ 206 ]; in humans hypocomplementaemia correlates with disease activity [ 207 ], and CFHR3/1 deletion is associated with susceptibility to SLE [ 208 ].…”
Section: Evidence For the Role Of Complement In The Tmasmentioning
confidence: 99%
“…The authors did not find an association with positive aPL. However, patients with TMA had worse renal prognosis ( 62 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed lymphopenia and anti-Ro positivity as independent risk factors for developing renal TMA. It also showed no significant difference in outcomes for patients with similar eGFR with or without TMA, and no significant effect on renal survival in TMA patients [18]. A study out of Northern Taiwan including 2461 SLE patients highlighted infection as a potential major trigger for TMA occurrence [9].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, Barrera-Vargas et al [18] attempted to identify possible risk factors contributing to TMA in SLE patients, and further define TMA's impact on clinical outcomes. This study showed lymphopenia and anti-Ro positivity as independent risk factors for developing renal TMA.…”
Section: Discussionmentioning
confidence: 99%